DRTA STRATEGY ON STUDENTS’ READING COMPREHENSION - Moh Hanafi; Ayu Rizki Septiana (JURNAL EDUSCIENCE (JES), 2022)
This research is aimed at investigating the effectiveness of Directed Reading Thinking strategy on students’ comprehension of academic reading. In order to be successful in reading comprehension, learners should actively process what they have read and it can be gained by certain practice and strategy. One of the strategy to be used is Directed Reading Thinking Activity which guide the students in making prediction before they read and confirming and refuting the prediction after reading the text. Using DRTA strategy, the students will be trained to be active and thoughtful readers. This research used pre experimental research design with one group pretest posttest design. The result of the hypothesis testing using paired sample t-test showed the significant value 0.002 is lower than level of significance 0.05. It means H0 is rejected and it can be stated that there is a significant difference on the students’ reading comprehension after being taught using DRTA strategy. Thus, it can be concluded that DRTA strategy was effective to teach reading comprehension.